Research and advanced technology for digital libraries : 9th European Conference, ECDL 2005, Vienna, Austria, September 18-23, 2005 : proceedings - ECDL; Rauber, Andreas; Christodoulakis, Stavros; Tjoa, A Min (Lecture notes in computer science, 2005)
This book constitutes the refereed proceedings of the 9th European Conference on Research and Advanced Technology for Digital Libraries, ECDL 2005, held in Vienna, Austria in September 2005. The 41 revised full papers presented together with 2 panel papers and 30 revised poster papers were carefully reviewed and selected from a total of 162 submissions. The papers are organized in topical sections on digital library models and architectures, multimedia and hypermedia digital libraries, XML, building digital libraries, user studies, digital preservation, metadata, digital libraries and e-learning, text classification in digital libraries, searching, and text digital libraries.